2014
DOI: 10.1007/s00431-014-2318-2
|View full text |Cite
|
Sign up to set email alerts
|

How common are long-lasting, intensely itching vaccination granulomas and contact allergy to aluminium induced by currently used pediatric vaccines? A prospective cohort study

Abstract: Long-lasting itching vaccination granulomas are poorly understood but more frequent than previously known after infant vaccination with commonly used diphtheria-tetanus-pertussis-polio-Haemophilus influenzae type b and pneumococcal conjugate vaccines. The risk increases with the number of vaccines given. Most children with itching granulomas become contact allergic to aluminium. Itching vaccination granulomas are benign but may be troublesome and should be recognised early in primary health care to avoid unnec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 32 publications
5
87
0
6
Order By: Relevance
“…Finally, in vivo studies showed the capacity of these systems to trigger efficient immune responses 49 against the hepatitis B antigen following intramuscular administration, suggesting the potential interest 63 unwanted side effects, i.e. local reactions or hypersensitization in 64 allergic patients and (iv) limited thermostability [1,2]. Due to these 65 limitations, significant efforts have been made to develop alterna-66 tive adjuvants.…”
mentioning
confidence: 99%
“…Finally, in vivo studies showed the capacity of these systems to trigger efficient immune responses 49 against the hepatitis B antigen following intramuscular administration, suggesting the potential interest 63 unwanted side effects, i.e. local reactions or hypersensitization in 64 allergic patients and (iv) limited thermostability [1,2]. Due to these 65 limitations, significant efforts have been made to develop alterna-66 tive adjuvants.…”
mentioning
confidence: 99%
“…Aluminum salts increase the Th2‐mediated antibody response to the desired antigen and have been used as adjuvants in vaccines since the 1920s (Table ). Injection‐associated granulomas are a rare side effect of immunizations, with reported frequencies of 0.35%‐1.18% . Although this reaction is more commonly reported in young children, probably because of their frequent vaccination schedule, adults have presented with similar findings after allergen immunotherapy and human papilloma virus vaccination, which both contain aluminum adjuvants .…”
Section: Discussionmentioning
confidence: 99%
“…Bergfors et al ont effectué une étude prospective chez près de 5000 enfants vaccinés par ce même type de vaccin (Infanrix-5 ® ou Pentavac ® ), associé ou non au vaccin anti-pneumococcique (Prevenar ® ), dans le but de déterminer la prévalence des nodules persistants et leur durée, ainsi que la prévalence et la durée des sensibilisations à l'hydroxyde d'aluminium chez les enfants porteurs de nodules [69]. Trente-huit enfants (0,83 %) ont développé des nodules sous-cutanés inflammatoires et prurigineux, persistant en moyenne pendant 22 mois (extrêmes : 6-43 mois), et associés à une pigmentation anormale ou une décoloration de la peau, une hypertrichose et/ou un eczéma dans 8 cas (21 %).…”
Section: Vaccinsunclassified